In the shadows of the American century : the rise and decline of US global power - McCoy, Alfred W. (Quezon City, Philippines : Ateneo De Manila University Press, 2017)
"In a completely original analysis, prize-winning historian Alfred W. McCoy explores America's rise as a world power--from the 1890s through the Cold War--and its bid to extend its hegemony deep into the twenty-first century through a fusion of cyberwar, space warfare, trade pacts, and military alliances. McCoy then analyzes the marquee instruments of US hegemony--covert intervention, client elites, psychological torture, and worldwide surveillance. Peeling back layers of secrecy, McCoy exposes a military and economic battle for global domination fought in the shadows, largely unknown to those outside the highest rungs of power."--Page 4 of cover.
Understanding the US Empire. The world island and the rise of America -- "Our S.O.B.s" : America and the autocrats -- Covert netherworld -- US Strategies for Survival. A global surveillance state -- Torture and the eclipse of empires -- Beyond bayonets and battleships : the Pentagon's wonder weapons -- Dynamics of US Decline. Grandmasters of the great game -- Five scenarios for the end of the American century.
Includes bibliographical references and index.
Keywords: BALANCE OF POWER -- FORECASTING